Virtual inertia control to active support of the variable-speed wind turbine in variable frequency limit time - Tingyun, Gu; Houyi, Zhang; Bowen, Li; Junyi, Mao; Qiang, Fan; Yutao, Xu; Qihui, Feng (Frontiers in Energy Research, 2024)
Constraining the virtual inertia of variable-speed wind turbines within the variable frequency limit time will be the key to improving the wind power’s reliability in actively supporting the system frequency. First, this paper analyzes the controllable characteristics and evaluation methods of the virtual inertia of the wind turbine. Second, it quantifies the variable frequency limit time of the grid with high-proportion wind power and considers the wind turbine speed and power margin to restrict the virtual inertia of the wind turbine during the period of frequency drop or increase to provide reliable inertia support to ensure the safety of the system frequency. On this basis, the inertia demand under the frequency safety of the system was analyzed, and the virtual inertia control strategy of the variable-speed wind turbine in the variable frequency limit time was proposed using the speed tracking performance of the wind turbine. Finally, the grid with a high-proportion wind power simulation system is built to verify that the variable-speed wind turbine can reliably satisfy the inertia demand of system frequency modulation under the proposed control strategy and significantly improve its active support performance to the power grid.